2022
DOI: 10.3389/fonc.2022.968517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histology on the efficacy of immune checkpoint inhibitors in advanced non-small cell lung cancer: A systematic review and meta-analysis

Abstract: BackgroundLittle is known about the effect of histology on the efficacy of immune checkpoint inhibitors (ICI) in non-small-cell lung cancer (NSCLC). We conducted a systematic review and meta-analysis to assess the potential differences in the efficacy of ICIs between squamous NSCLC (SQ-NSCLC) and non-squamous NSCLC (non-SQ-NSCLC).MethodsSystematic searches of PubMed, Embase, Scopus, and Cochrane Library databases were conducted. All randomized clinical trials of ICIs with available hazard ratios (HR) for progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The application of cancer immunotherapy has achieved clinical advances and proven antitumor effects for melanoma, NSCLC renal cell carcinoma, head and neck squamous cell carcinoma, urothelial cell carcinoma, colorectal cancer, and others [ 13 , 42 , 43 ]. The effect of ICIs on histological types of NSCLC has been reported, and a meta-analysis revealed that both non-LUSC and LUSC responded to ICIs, with LUSC showing a greater response [ 13 ]. However, another meta-analysis of smaller size reported that non-LUSC showed a greater response to ICI treatment in previously untreated patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of cancer immunotherapy has achieved clinical advances and proven antitumor effects for melanoma, NSCLC renal cell carcinoma, head and neck squamous cell carcinoma, urothelial cell carcinoma, colorectal cancer, and others [ 13 , 42 , 43 ]. The effect of ICIs on histological types of NSCLC has been reported, and a meta-analysis revealed that both non-LUSC and LUSC responded to ICIs, with LUSC showing a greater response [ 13 ]. However, another meta-analysis of smaller size reported that non-LUSC showed a greater response to ICI treatment in previously untreated patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of lung ICI monotherapy found that the hazard ratio (HR) for OS and the 95% confidence interval (CI) for non-LUSC and LUSC were 0.80, 95% CI 0.73–0.87 and 0.71, 95% CI 0.65–0.77, respectively. In addition, the HR (95% CI) for PFS was 0.90 (0.76–1.07) for non-LUSC and 0.65 (0.56–0.77) for LUSC [ 13 ]. These combined results for ICI monotherapy showed better OS and PFS for LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization guidelines, MpBC is classified into various subtypes based on its cytopathological features and cell differentiation [1]. In this particular case, squamous cell differentiation may have contributed to the remarkable response to IO, as IO has been proven effective in squamous carcinomas across different tumor subtypes, such as cervical, lung, and head and neck cancers [18][19][20][21]. However, due to financial constraints, we lacked information on the expression of TILs and TMB in this case, which are important factors that could have shed light on the underlying mechanisms behind this dramatic response.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments and prognoses vary for NSCLC depending on the histological subtypes ( 4 ). For example, Li et al ( 5 ) found that in comparison to non-SQ-NSCLC, ICI monotherapy for SQ-NSCLC led to a noticeably greater survival rate. In addition, Baine et al ( 6 ) showed that SCC is independently linked to an increased risk of death, and patients with SCC who have received SBRT treatment are at an elevated risk of both local and distant failure.…”
Section: Introductionmentioning
confidence: 99%